Manajemen Pemeliharaan di Fasilitas Koloni Asuransi - Ajaib Trisakti Teuf; Ludji Michael Riwu Kaho; Oki Hidayat (Wana Lestari, 2025)
The Insurance Colony Facility (FKA) is an ex-situ conservation center aimed at preparing the Rote snake-necked turtle (Chelodina mccordi), an endemic Indonesian species classified as critically endangered and possibly extinct in the wild (CR-PEW), for reintroduction into its natural habitat. This study employed a morphometric measurement method to evaluate the growth and development of C. mccordi individuals at the Insurance Colony Facility. The study aims to assess the growth of C. mccordi individuals during quarantine and habituation by measuring body weight, carapace dimensions, plastron size, and body circumference. The results indicate that the Rote snake-necked turtles experienced normal growth across most variables. The highest growth rates were recorded in plastron length, which reached 1.4 cm, and in head-to-body length for individuals 2 and 3.